2007
DOI: 10.1002/qj.123
|View full text |Cite
|
Sign up to set email alerts
|

Applications of information theory in ensemble data assimilation

Abstract: ABSTRACT:We apply information theory within an ensemble-based data assimilation approach and define information matrix in ensemble subspace. The information matrix in ensemble subspace employs a flow-dependent forecast error covariance and it is of relatively small dimensions (equal to the ensemble size). The information matrix in ensemble subspace can be directly linked to the information matrix typically used in non-ensemble-based data assimilation methods, such as the Kalman Filter (KF) and the three-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 63 publications
1
51
0
Order By: Relevance
“…Inversion of fluxes from concentrations to derive surface fluxes using transport models has already proved capable of providing global-scale, and in some instances continentalscale, information on fluxes with uncertainties. Some pilot studies have applied atmospheric inversion models at a finer scale down to ∼ 1 km, constrained by regionally denser atmospheric measurements (Schmitgen et al, 2004;Zupanski et al, 2007;Lauvaux et al, 2012;Göckede et al, 2010;Broquet et al, 2011;Lauvaux et al, 2009). However, the current sparseness of the ground-based network of atmospheric stations cannot constrain the patterns of CO 2 sources and sinks at the scale of nations, states/provinces, or cities (Hungershoefer et al, 2010;Chevallier et al, 2010), although some country-level estimates have been derived for CH 4 in Europe (Bergamaschi et al, 2010).…”
Section: )mentioning
confidence: 99%
“…Inversion of fluxes from concentrations to derive surface fluxes using transport models has already proved capable of providing global-scale, and in some instances continentalscale, information on fluxes with uncertainties. Some pilot studies have applied atmospheric inversion models at a finer scale down to ∼ 1 km, constrained by regionally denser atmospheric measurements (Schmitgen et al, 2004;Zupanski et al, 2007;Lauvaux et al, 2012;Göckede et al, 2010;Broquet et al, 2011;Lauvaux et al, 2009). However, the current sparseness of the ground-based network of atmospheric stations cannot constrain the patterns of CO 2 sources and sinks at the scale of nations, states/provinces, or cities (Hungershoefer et al, 2010;Chevallier et al, 2010), although some country-level estimates have been derived for CH 4 in Europe (Bergamaschi et al, 2010).…”
Section: )mentioning
confidence: 99%
“…Zupanski et al (2007) showed that this formula could also be useful in reduced-rank, ensemble space calculations, in which the summation is performed over the number of ensemble members. Since an eigenvalue decomposition of the observation information matrix is a component of the MLEF algorithm, the additional cost of calculating d s is minimal.…”
Section: Information Content Of Lightning Observationsmentioning
confidence: 99%
“…In the following, we will show the square root of error variance reduction, i.e., diag(C) (referred to as observation impact signal or OIS in the following) for different variables at different levels. Similar quantities, such as information content, relative entropy, degrees of freedom for signal, and mutual information, for quantifying the impacts of observations in a DA system have been introduced and studied by Rodgers (2000), Xu (2007), Zupanski et al (2007) and Fowler and van Leeuwen (2012).…”
Section: Eigenvalues and Eigenvectorsmentioning
confidence: 99%